2016
DOI: 10.1016/j.ijid.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Daclatasvir plasma level and resistance selection in HIV patients with hepatitis C virus cirrhosis treated with daclatasvir, sofosbuvir, and ribavirin

Abstract: Sub-optimal DCV drug levels allow the selection of resistance-associated variants and fail to contribute to antiviral activity. No definite reason for the low DCV level was found. Quantifying the drug is suggested in difficult-to-treat patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…This plasma was obtained at steady state, just before the morning intake of the drug (Ctrough). This method is currently used as a part of our routine TDM of DCV for both HCV-infected and HCV/HIV-coinfected patients [22]. These data confirm the clinical applicability of the present analytical method.…”
Section: Analysis Of Patient Samplessupporting
confidence: 76%
“…This plasma was obtained at steady state, just before the morning intake of the drug (Ctrough). This method is currently used as a part of our routine TDM of DCV for both HCV-infected and HCV/HIV-coinfected patients [22]. These data confirm the clinical applicability of the present analytical method.…”
Section: Analysis Of Patient Samplessupporting
confidence: 76%
“…In regard to NS5A sequence from HCV GT 3a, substitution A30S has previously been reported by Malta F. et al . (2017) [11] in a viral sequence of a HCV GT 3a/HIV non-responder coinfected patient (baseline prevalence of 6.7%; 1/15) and in an international case report [24]. In the present study, we found RAS A30S in one GT 3a non-responder patient, however, the inexpressive number of GT 3a patients available in our study (n = 4) prevented us to verify whether this substitution is common in HCV strains circulating in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study exploring ribavirin TDM in decompensated cirrhotic individuals treated with new DAAs regimens and showing an overexposure in this group of patients. Indeed, while few data report RBV plasma levels in therapeutic range in patients with Child-Pugh A treated with a fixed dose (800 mg daily) of RBV associated with SOF and DCV[ 19 ], no information about Child-Pugh B or C patients are currently available. These findings might be useful to clinicians, since an overexposure can be modulated by lowering the initial RBV dosage from the weight-based dosage in certain patients with advanced liver disease, avoiding secondary and detrimental effects.…”
Section: Discussionmentioning
confidence: 99%